2020
DOI: 10.1007/s00062-020-00898-y
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Stenting as Definitive Treatment for Free Floating Thrombus—Review of 7 Cases

Abstract: Background and Purpose Free floating thrombus (FFT) is a rare condition. The optimal treatment strategy is yet to be determined although medical management with anticoagulation is the mainstay. This article reports experience of treating FFT with carotid stenting. Methods A retrospective analysis of a prospectively maintained database was performed to identify all patients with FFT treated with carotid stenting. For each patient the demographic data, clinical presentation, location of the thrombus, type of ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…Although, as the patients have benefits from the anticoagulation and antiplatelet therapy or surgical approaches in previous reports. 4 , 5 Which is the most appropriate management for FFT still needs to be individualized by detailed arterial imaging evaluation and dynamic monitoring of the thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…Although, as the patients have benefits from the anticoagulation and antiplatelet therapy or surgical approaches in previous reports. 4 , 5 Which is the most appropriate management for FFT still needs to be individualized by detailed arterial imaging evaluation and dynamic monitoring of the thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…Оптимальну стратегію лікування не визначено через рідкісність захворювання, а також брак порівняльних досліджень консервативного (антикоагулянтна та/або дезагрегантна терапія) і хірургічного лікування (стентування сонної артерії, ендоваскулярна тромбектомія, ендартеректомія) [6].…”
Section: клінічні випадкиunclassified
“…5 There have been several recent reports about the successful mechanical thrombectomy of CFFT. [6][7][8][9][10][11][12][13][14][15][16][17] These studies have demonstrated the challenges of safely performing mechanical thrombectomy due to significant clot burden, lack of tools, and techniques designed to perform cerebrovascular thrombectomy. In total, the literature to date has provided no conclusive techniques for safe and reliable removal of CFFTs.…”
mentioning
confidence: 99%
“…In total, the literature to date has provided no conclusive techniques for safe and reliable removal of CFFTs. 5,18 Recent technological improvements in aspiration catheters and stentrievers has made mechanical thrombectomy of cerebral vessels increasingly safe [6][7][8][9][10][11][12][13][14][15][16][17] and effective. 19,20 Among these developments are large-bore aspiration catheters (0.088" ID) 21,22 that are built both with and without compliant balloons for flow arrest and aspiration/flow reversal.…”
mentioning
confidence: 99%